Search for the decays B0s→[tau]+[tau]− and B0→[tau]+[tau]− - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; De Cian, Michel; Comerma-Montells, Albert; Esen, Sevda; Färber, Christian; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2017)
A search for the rare decays B0s→τ+τ− and B0→τ+τ− is performed using proton-proton collision data collected with the LHCb detector. The data sample corresponds to an integrated luminosity of 3 fb−1 collected in 2011 and 2012. The τ leptons are reconstructed through the decay τ−→π−π+π−ντ. Assuming no contribution from B0→τ+τ− decays, an upper limit is set on the branching fraction B(B0s→τ+τ−)<6.8×10−3 at the 95% confidence level. If instead no contribution from B0s→τ+τ− decays is assumed, the limit is B(B0→τ+τ−)<2.1×10−3 at the 95% confidence level. These results correspond to the first direct limit on B(B0s→τ+τ−) and the world’s best limit on B(B0→τ+τ−).
Im Titel wird "tau" als griechischer Buchstabe dargestellt
Im Titel sind "+", "-" und "0" hochgestellt
Im Titel sind "0" und "s" übereinander geschrieben, wobei "0" oben und "s" unten steht
Gesehen am 31.08.2018
R. Aaij, P. d'Argent, S. Bachmann, S. Braun, A. Comerma-Montells, M. De Cian, S. Esen, C. Färber, D. Gerick, E. Gersabeck, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, R. Kopecná, P. Krokovny, C. Langenbruch, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Schilller, P. Seyfert, M. Stahl, S. Stemmle, J. von Tilburg, U. Uwer, R. Waldi, A. Zhelezov [und weitere]